Canadian content : culture and the quest for nationhood - Edwardson, Ryan, 1974- (Book collections on Project MUSE., 2008)
Canadian Content looks at Canada as an ongoing postcolonial process of not one but a series of radically different nationhoods, each with its own valued but tentative set of cultural criteria for orchestrating and implementing a Canadian national experience.